KESALAHAN PENERJEMAHAN KALIMAT NEGASI BAHASA INGGRIS: SEBUAH KAHAN SINTAKSIS DAN SEMANTIS - Santy Yulianti (Widyariset, 2009)
This study analyses the translation mistakes of negation sentences of Mary Higgins Clark's novel entitled "stiilwatch". The target novel is translated by Juni Sohardjo. The study is clasified into semantic and sintactic analysis using descriptive comparative method. Data were collected and classified into negation scope according to Quirk's theory and analyses the translation forms in the Indonesian novel. Most of sentences from the target language of this novel use free form of the translation that have changed the structure and meaning of the original novel.